1984
DOI: 10.1007/bf01015208
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte count and hemoglobin levels in diabetic women

Abstract: Fasting blood glucose, erythrocyte counts hemoglobin levels of 131 Libyan diabetic women of Tripoli , Libya were determined. The respective mean values were 223 +/- 7 mg X dl-1, 4.97 +/- 0.034 X 10(6) X mm-3 and 14.4 +/- 0.127 g X dl-1. Sixty-five percent of these diabetic women were obese. The highest percent of diabetics belong to the age group 46-55 years. The increase in prevalence of diabetes correlates with an increase in obesity. A significant positive correlation was found between body surface area and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…A notable limitation is the lack of data on maternal anaemia. Data from previous studies suggest that increased haemoglobin is associated with increased risk of glucose intolerance, diabetes and GDM, [40][41][42] and one study which found no difference in the incidence of GDM between anaemic and non-anaemic women found women with ID anaemia had about one-half the incidence of GDM compared with non-anaemic women. 43 The relationship between anaemia and GDM is not well understood and requires further study.…”
Section: Discussionmentioning
confidence: 94%
“…A notable limitation is the lack of data on maternal anaemia. Data from previous studies suggest that increased haemoglobin is associated with increased risk of glucose intolerance, diabetes and GDM, [40][41][42] and one study which found no difference in the incidence of GDM between anaemic and non-anaemic women found women with ID anaemia had about one-half the incidence of GDM compared with non-anaemic women. 43 The relationship between anaemia and GDM is not well understood and requires further study.…”
Section: Discussionmentioning
confidence: 94%
“…25,26,28) Zahir et al have reported that hematocrit and red blood cell count significantly influenced the percentage of tacrolimus associated with erythrocytes and the fraction of unbound tacrolimus was correlated with ¡1-acid glycoprotein and high density lipoprotein cholesterol concentrations. 28) There are several reports suggesting that erythrocyte counts are increased in obese patients compared with non-obese patients, [29][30][31] although no clear effect of obesity on hematocrit has been reported. Moreover, laboratory data provided by the breeder of Zucker rats suggested no significant difference in erythrocyte counts or hematocrit between lean and obese Zucker rats.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] A strong association between psoriasis, overweight obesity, and cardiovascular co-morbidities has been proposed. [13][14][15][16] Obesity is a proinflammatory state, presenting as a low-grade, chronic inflammatory condition that might further enhance inflammation in psoriatic patients; [17,18] it might also stimulate erythropoiesis to increase the number of circulating red cells [19] to face the higher oxygen requirements, due to the increase in body mass.…”
Section: Introductionmentioning
confidence: 99%